(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
This work intends to sew content resulting from an ethnographic immersion in the popular “rolezinhos” of the “Passinho dos Maloka” in Rua Tauá, peripheral region of the Santo Amaro neighborhood, in the city of Recife, Pernambuco, in February 2020, as well as the “post -rolê ”in the vicinity of the “baile”, which is located in the neighboring city of Olinda. It is discussed here, in addition to evoking the flowering of the phenomenon of “Passinho” and “bregafunk” at the national level, aesthetics, especially dressing, as a device for identity construction, the sexualized body narratives through the rhythmic dance by the groups of subjects, racialization, gender, peripheral culture in Pernambuco, as well as the dreaded “rolês” finals, which are not always very positive.